DFT Calculations for the HONO Elimination Process of CL-20 Conformers. (22nd December 2021) - Liu, Lin-Lin; Zhang, Tong-Yong; Hu, Song-Qi
Abstract : The HONO elimination process is regarded to be an important initial decomposition process of energetic nitramines. Four CL-20 conformers based on the ε -CL-20 were obtained by the optimization at the m062x/cc-pvtz level in this study, and the Transition State (TS) and Intrinsic Reaction Coordinate (IRC) calculations were carried out at the same level. In addition, the rate coefficients and activation energy of the HONO elimination process were evaluated using conventional transition state theory (TST) and canonical variational transition state theory (CVT) with Eckart and small-curvature tunneling (SCT) methods to correct the transmission coefficients for the quantum tunneling effect. The calculation results have shown that the HONO elimination process concerning the nitro groups located on six numbered rings is the hardest to happen, and it seems that the longer distance between nitro groups and the adjacent hydrogen atom would result in the higher barrier energy; the HONO elimination process is most likely to happen for the axial positioning of nitro groups located on five numbered rings and most unlikely to happen for the ones located on six numbered rings; CL-20 II and CL-20 IV conformers are the most unstable one and most stable one concerning the reaction difficulty of the HONO elimination process.